Systematic review: Relationships between sleep and gastro-oesophageal reflux - Dent, J.; Holloway, R.; Eastwood, Peter (2013)
Background Gastro-oesophageal reflux disease (GERD) adversely impacts on sleep, but the mechanism remains unclear. Aim To review the literature concerning gastro-oesophageal reflux during the sleep period, with particular reference to the sleep/awake state at reflux onset. Methods Studies identified by systematic literature searches were assessed. Results Overall patterns of reflux during the sleep period show consistently that oesophageal acid clearance is slower, and reflux frequency and oesophageal acid exposure are higher in patients with GERD than in healthy individuals. Of the 17 mechanistic studies identified by the searches, 15 reported that a minority of reflux episodes occurred during stable sleep, but the prevailing sleep state at the onset of reflux in these studies remains unclear owing to insufficient temporal resolution of recording or analysis methods. Two studies, in healthy individuals and patients with GERD, analysed sleep and pH with adequate resolution for temporal alignment of sleep state and the onset of reflux: all 232 sleep period reflux episodes evaluated occurred during arousals from sleep lasting less than 15 s or during longer duration awakenings. Six mechanistic studies found that transient lower oesophageal sphincter relaxations were the most common mechanism of sleep period reflux. Conclusions Contrary to the prevailing view, subjective impairment of sleep in GERD is unlikely to be due to the occurrence of reflux during stable sleep, but could result from slow clearance of acid reflux that occurs during arousals or awakenings from sleep. Definitive studies are needed on the sleep/awake state at reflux onset across the full GERD spectrum. © 2013 John Wiley & Sons Ltd.